Transforming Human and Social Capital into Value the Mediating Role of Organizational Learning in Education SMEs—Evidence from Shandong Province, China - Jiang, Lijuang; Suo, Lu (Rajapark Journal, 2025)
This study examines how human capital (HC) and social capital (SC) influence value capturing (BVCA) and value delivery (BVDE) in education SMEs, with a focus on the mediating role of organizational learning (OL). Using data from 526 senior managers in Shandong Province, China, analyzed via PLS-SEM, the study reveals that both HC and SC have significant direct effects on BVCA and BVDE (β= 0.125–0.163, p < 0.01). More importantly, OL serves as a strong mediator, with indirect effects ranging fromβ= 0.189 to 0.212 (p < 0.001). These findings underscore the critical role of OL in converting static resources into dynamic value outcomes. The study integrates Resource-Based View and Dynamic Capabilities Theory, proposing a "Weak Resources–Strong Mechanisms" framework that emphasizes practical OL practices—such as knowledge sharing, R&D integration, and external collaboration—to help SMEs enhance value creation and competitiveness. This research offers actionable insights for education SMEs operating in resource-constrained environments.